Distal Radioulnar Joint Interposition Arthroplasty for Primary Distal Radioulnar Joint Arthritis - Carlson Strother, Courtney R.; Kakar, Sanjeev (Journal of Wrist Surgery, 2023)
Background Surgical management of the painful, arthritic distal radioulnar joint (DRUJ) remains challenging, particularly in young, active patients.Description of Technique Following exposure of the DRUJ through a dorsal longitudinal incision over the DRUJ, suture anchors are evenly placed around the sigmoid notch. The sutures are threaded through the dermal allograft to secure the graft into the sigmoid notch. The volar edges of the allograft are passed from radial to ulnar underneath the distal ulna and secured to the remaining allograft dorsally, reducing the DRUJ and creating a stable interposition arthroplasty.Patients, Methods, and Results We present a case report of a young, manual laborer who had significant improvement in pain, range of motion, and grip strength 6 months following interposition arthroplasty at the DRUJ. He was able to return to work after completing his rehabilitation following surgery.Conclusions Dermal allograft interposition arthroplasty may provide reliable pain relief while maintaining pronosupination and stability of the DRUJ in the appropriately selected patient, without the need for lifting restrictions.
Keywords: allograft; interposition arthroplasty; DRUJ; arthritis